Extract the glue material from the fig plant and study its physico-chemical qualities - Ayoub, Afaf Abdel Rahman; Khalil, Rana Riad; Hassan, Fiziawi Sari Sami (Journal of agricultural, environmental and veterinary sciences, 2017)
The study aimed to identify those qualities on the chemical contents and functional properties and effects of laser rays 532nm milk figs, Where the tests were conducted for studying the physic - chemical characteristics of the milk in Fig in the Labs of the Environment Research Center / University of Technology. We found that chemical contents of the milk were 2.166 % protein and 51.96 % moisture and 4.09 ash and 0.28 fat as T.S.S 40.33% recorded while the pH was 4.98 while the functional properties of the score of the melting 75.93 % and viscosity 44.98 Centipois and water absorption 2.32 ml of water / g sample while linking fat 0.67 ml oil / g by increasing the sample The gels have increased up to focus where the highest percentage at a concentration of 3 %. As for the results of fig milk after exposure to radiation may be given to the viscosity less lost viscosity recorded after exposure the laser 23.67Centipoins. And the proportion of melting has increased, becoming an 88.52 %.